P001 Immune checkpoint inhibitor-induced colitis is mediated by polyfunctional lymphocytes and is dependent on the IL23/IFNg axis. (21st January 2022) - Lo, J; Cozzetto, D; Madgwick, M; Sieh, J Y X S; Olbei, M; Alexander, J L; Miguens Blanco, J; Kudo, H; Ibraheim, H; Liu, Z; Castro Seoane, R; Goldin, R; et al.
Abstract: Background: Immune checkpoint inhibitors (CPI) have revolutionised cancer treatment, with previously untreatable disease now amenable to potential cure. Combination regimens of anti-CTLA4 and anti-PD-1 show enhanced efficacy but are prone to off target immune-mediated tissue injury, particularly at the barrier surfaces. CPI-induced colitis is a common a serious complication. Methods: To probe the impact of immune checkpoints on intestinal homeostasis mice were challenged with combination anti-CTLA4 and anti-PD-1 immunotherapy, manipulation of the intestinal microbiota and antibody blockade/depletion studies. Colonic immune responses were profiled using RNA-sequencing, including high-resolution single cell analyses, and flow cytometry. Results: CPI colitis was dependent on the composition of the intestinal microbiota and was characterized by remodelling of mucosal lymphocytes with induction of polyfunctional lymphocyte responses characterized by expression of interferon-g (IFNg), other pro-inflammatory cytokines/chemokines ( Il22, Il17a Ccl3, Ccl4 and Ccl9 ) and cytotoxicity molecules ( Gzmb, Gzma, Prf1, Nkg7 ). In comparison with mucosal lymphocytes in the steady state, polyfunctional lymphocytes from both CD4 + and CD8 + lineages upregulated costimulatory molecules and checkpoint molecules in CPI-colitis, indicating that these cells are usually very tightly regulated. CPI-colitis was attenuated following depletion of effector lymphocytes or following blockade of the IL23/IFNg axis. Conclusion: This study provides new mechanistic insights into CPI-colitis, identifying polyfunctional, cytotoxic lymphocytes as key mediators of disease. Therapeutic targeting of their effector response or regulatory networks, including the IL23/IFNg axis holds the key to preventing and reversing CPI-colitis.